TRANSLATION EVALUATION IN A NEWS AGENCY. - Hajmohammadi, Ali (Perspectives: Studies in Translatology, 2005)
In this article, I argue that most approaches to translation evaluation that are central to Translation Studies scholars and teachers are out of touch with market demands. I present the working conditions of translators in a news agency and discuss the evaluation of translation performance in the market. I am particularly keen on calling attention to the differences between academic and market parameters for evaluation. First, there is a presentation of the purpose of evaluation in news agency environments and subsequently, I describe the assessment of news translation. I finish by examining two parameters of evaluation, which, in my opinion, distinguish translation evaluation in the market from the academy. The suggestions are based on my observations as a translation evaluator in IRIB news agency, Tehran.